Evaluación preliminar del conocimiento ancestral de la cría de abejas nativas amazónicas y producción de miel en la ciudad de Moyobamba – Región San Martín. 2022 - Vasquez Pinedo, Tito Guillermo (2023)
In the city of Moyobamba located in the San Martín region, the present work is developed, the objective is to investigate the ancestral knowledge of the breeding of native Amazonian bees in the residents of the city of Moyobamba, in the natural environment. It is concluded that the people in the study have a high level of knowledge of the breeding of native bees in the natural environment, they know the meliponera species, nesting sites, honey harvest times, sex of the insects, natural feeding, and they recognize the sex , species of plants that serve as food and therefore maintain nearby forests by planting fruit trees, learned by direct observation the natural breeding of bees, being motivated in schools and higher institutes and by family tradition. They identify 31 to 40 colonies per year (40%) and 21 to 30 hives per year (20%), whether in secondary or primary forests (80%), and harvest honey from June to November (80%), using This is manual tools for extracting honey from the “nideras”, with times of one hour. One hive generates 2 Kg honey/hive, (4 bottles of 626 ml.). They check the hives before exploitation, if there are bees around, entry free of dead bees and wax, (non-sick swarm), presence of queen and larvae, there is honey production inside. They relate to temperature, humidity and rainfall, as factors that affect bee production, in addition to knowing that deforestation, use of agrochemicals, forest fires, can decrease bee populations.